REFORMULASI SISTEM PENDIDIKAN PESANTREN DALAM MENGHADAPI GLOBALISASI DAN PASAR BEBAS - Zainal Efendi Hasibuan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2017)
Pesantren as society institutions is believed to be an institution that can still exist in the face of globalization and the free market. Pesantren has a function hang of religious sciences and formed a noble character. Responding to the changing times in the present context, schools need to determine takhassusnya that is not too difficult to get the students due to the proliferation of Islamic boarding schools in Indonesia; schools are required to teach life skills based on local needs and demands of society; schools need to work with various stakeholders to improve the quality of education schools; mastery of Arabic and English is a must; schools need to formulate a vision, mission, goals, short and long term objectives, and evaluate each work program.